Efficacy of an alcohol-focused intervention for improving adherence to antiretroviral therapy (ART) and HIV treatment outcomes - a randomised controlled trial protocol - Parry, C.D.H.; Morojele, N.K.; Myers-Franchi, Bronwyn; Kekwaletswe, C.T.; Manda, S.O.M.; Sorsdahl, K.; Ramjee, G.; Hahn, J.A.; Rehm, J.; Shuper, P.A. (2014)
Background: Little research has examined whether alcohol reduction interventions improve antiretroviral therapy (ART) adherence and HIV treatment outcomes. This study assesses the efficacy of an intervention for reducing alcohol use among HIV patients on ART who are hazardous/harmful drinkers. Specific aims include adapting a blended Motivational Interviewing (MI) and Problem Solving Therapy (PST) intervention for use with HIV patients; evaluating the efficacy of the intervention for reducing alcohol consumption; and assessing counsellors' and participants' perceptions of the intervention.